How Enhancing Employee Well-Being Can Encourage Voice Behavior: A Desire Fulfillment Perspective. Issue 5 (19th October 2020) - Duan, Jinyun; Wang, Xiaotian; Brinsfield, Chad T.; Liu, Susu
ABSTRACT: Drawing on desire fulfillment theory, we develop and test a model of employee well-being and voice behavior. Our findings indicate that psychological meaningfulness and perceptions of social worth are positively related to employee well-being. Moreover, these relationships are stronger when psychological safety is higher. Our findings also indicate that when employee well-being is higher there is an increased likelihood that employees will express voice. Moreover, this relationship is stronger when employee perspective taking is higher. Lastly, moderated-mediation analyses indicate that well-being mediates the relationships between psychological meaningfulness and voice, and between social worth and voice, and these effects are stronger when psychological safety and perspective taking are both higher. Implications for theory and practice are discussed.